Structural behaviour and continuous strength method design of high strength steel non-slender welded I-section beam–columns. (December 2021) - Tse, Kevin; Wang, Jie; Yun, Xiang
Abstract: This paper presents the development of efficient design equations for high strength steel (HSS) welded I-section beam–columns under the framework of the Continuous Strength Method (CSM). The present work includes a collection of available experimental data on HSS S690 and S960 welded I-section beam–columns and a comprehensive numerical modelling programme considering a wider spectrum of parameters that influence the structural behaviour of the HSS welded I-section beam–columns. The developed FE models were first validated against test results collected from the literature, after which parametric studies were performed to generate further results to assess the accuracy of the codified design methods as used in Europe and the US, as well as to underpin new design proposals for HSS non-slender welded I-section beam–columns. It has been shown that the proposed CSM-based design approach is able to provide reliable design predictions with improved accuracy and reduced scatter over the existing design methods, and its reliability has been confirmed by means of statistical analyses. Highlights: Numerical models validated against test results for HSS beam–columns. Validated numerical models used to perform parametric studies considering key parameters. Current European and American design provisions assessed using the experimental and numerical data. The Continuous Strength Method extended to cover the design of HSS beam–columns with welded I-sections. Reliability of the CSM evaluated by means of statistical analyses according to EN 1990.